2015
DOI: 10.1515/bap-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Structural power and the global financial crisis: a network analytical approach

Abstract: How did the most severe global financial crisis since the 1930s affect the organization of the world political economy? Was Anglo-American structural power in finance eroded? I employ network methodologies that have been recently extended for use with weighted and directed networks to shed light on these questions. I draw from complexity science and political economy to link these empirics to prior theories of structural power, which I refine in several ways. This approach provides unique explanations for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 68 publications
0
36
0
2
Order By: Relevance
“…Financial economists such as Allen and Babus (2009), computer systems experts such as Blume (2010), and political economists like Winecoff (2015) have examined how complex financial networks transmit financial crises through systemic transmission of risk and its resulting amplification. May et al (2008: 893) note that financial networks, like networks found in natural environments, ''are disassortative, in the sense that highly connected 'large' nodes tend to have their connections disproportionately with 'small' nodes; conversely, small nodes connect with disproportionately few large ones,'' and so the resulting ''sparseness of strong linkages can confer greater stability in systems whose components (nodes, banks, species) have some self-regulation.''…”
Section: The Nature Of Financial Network and Their Adaptive Agentsmentioning
confidence: 99%
“…Financial economists such as Allen and Babus (2009), computer systems experts such as Blume (2010), and political economists like Winecoff (2015) have examined how complex financial networks transmit financial crises through systemic transmission of risk and its resulting amplification. May et al (2008: 893) note that financial networks, like networks found in natural environments, ''are disassortative, in the sense that highly connected 'large' nodes tend to have their connections disproportionately with 'small' nodes; conversely, small nodes connect with disproportionately few large ones,'' and so the resulting ''sparseness of strong linkages can confer greater stability in systems whose components (nodes, banks, species) have some self-regulation.''…”
Section: The Nature Of Financial Network and Their Adaptive Agentsmentioning
confidence: 99%
“…Some scholars further studied the behavior of a network structure in financial contagion and proposed relevant measures to improve the stability of a financial system from the financial network angle by preparing policy guidance for preventing crisis-level contagion [2,4,7,19] (Wu et al, 2014; Chen et al, 2016). For example, Winecoff [21] studied the influence of global financial crises on politics and economics from a macro angle by establishing a complex network model. In addition, some works studied the stability of financial network.…”
Section: Related Literaturesmentioning
confidence: 99%
“…As I show in empirical examples below, structural prominence does not always lead to hypothesized policy outcomes. Prominence is an inherently positional concept, and is used regularly in network science, which, as demonstrated by Winecoff's (2015) contribution to this Issue, has great intuitive fit with the inherently relational concept of structural power. Prominence as a concept depends not on the discrete resources or capabilities that any one actor can "possess" but rather on a relationship among actors.…”
Section: Structural Prominence Vs Structural Powermentioning
confidence: 99%
“…See Bell and Hindmoor (2015), Young (2012). Helleiner (2014) has recently done so with respect to structural power arguments at the level of the international system, similar in some ways to the level of analysis of Winecoff (2015) the proposed regulation or being critical of it and arguing for changes. A positive plausibility test of H 1 would find that supporters of proposed regulations would be more structurally prominent firms, suggesting that these firms had more of their preferences catered to than less prominent ones.…”
Section: Analysis Of the Policy Agendamentioning
confidence: 99%